Improving made-in-China management research - Peng, Mike (2012)
Made-in-China products have a country-of-origin image of "low cost, cheap price, but only passable quality." What are the characteristics of Made-in-China management research? Passable (but not outstanding) quality seems to be a reasonable and accurate characterization of such research. How can the quality of Made-in-China management research be improved? I point out five common but fixable problems typically associated with such research, and offer actionable solutions to solve them. Finally, I argue that management scholars have a social responsibility to help improve China's country-of-origin image, by pursuing scholarly excellence and not tolerating sloppiness in management research.